2005
DOI: 10.1002/marc.200500614
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes as a Ligand in Cp2ZrCl2‐Based Ethylene Polymerization

Abstract: Summary: We report a simple method for tuning catalytic property of a metallocene‐based catalyst, Cp2ZrCl2, for ethylene polymerization by the direct adsorption of Cp2ZrCl2 onto multi‐walled carbon nanotubes (MWCNTs). The direct interactions between MWCNTs and the Cp rings of Cp2ZrCl2 controlled the polymerization behaviors, and we could generate polyethylene with an extremely high molecular weight ($\overline M _{\rm w}$ = 1 000 000) at 30 °C and under 1 atm of ethylene gas.Preparation of Cp2ZrCl2‐MWCNT.magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 41 publications
1
24
1
Order By: Relevance
“…Park et al used MWCNTs adsorbed with zirconocene to synthesize PE with high M w and MWD. The increase in M w was attributed to electronic and steric effect of MWCNTs [18]. Similarly, Stürzel et al [19] prepared UHMWPE by using functionalized graphene as a support for the single-site chromium catalyst.…”
Section: Crystallinity and Microstructure Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…Park et al used MWCNTs adsorbed with zirconocene to synthesize PE with high M w and MWD. The increase in M w was attributed to electronic and steric effect of MWCNTs [18]. Similarly, Stürzel et al [19] prepared UHMWPE by using functionalized graphene as a support for the single-site chromium catalyst.…”
Section: Crystallinity and Microstructure Analysismentioning
confidence: 97%
“…The highest M w is obtained with 10 mg of filler. The increase in the M w can be due to the steric and electronic effect of graphene [18,28]. It has been found that the M w of metallocene-polymerized polymers increases with electron donating effect [29].…”
Section: Crystallinity and Microstructure Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…[24] The molecular weight of the PE was found to be increased by this method. Based on these results, we reasoned that our method, using CNT-supported catalysts, should lead to the production of pristine CNT/ UHMWPE composites with a uniform dispersion of CNTs in a UHMWPE matrix, if the catalyst was properly chosen.…”
mentioning
confidence: 96%
“…CNT/polyethylene (PE) composites have been formed by ultrasonication, mechanical mixing of CNTs and melted polymers, [19][20][21] in situ polymerization with CNTs, [4] the use of functionalized CNTs to enhance the affinity of CNTs toward the polymer matrices, [22] and the use of catalysts or initiators immobilized onto CNTs. [23][24][25] However, as far as we know, the production of pristine CNT/UHMWPE composites has been unsuccessful up to now, because of the insolubility of UHMWPE, and its high viscosity in the melted form.…”
mentioning
confidence: 99%